Veterinary Anatomy and Physiology - Sian Rutland, Catrin; Kubale, Valentina (Veterinary Medicine and Science, 2019)
Knowledge of veterinary anatomy and physiology is essential for veterinary professionals and researchers. The chapters reflect the diverse and dynamic research being undertaken in a variety of different species throughout the world. Whether the animals have roles in food security, agriculture, or as companion, wild, or working animals, the lessons we learn impact on many areas of the profession. This book highlights research ranging from the cardiovascular and musculoskeletal systems, prostate and hoof, through to histopathology, imaging, and molecular techniques. It investigates both healthy and pathological conditions at differing stages of life. The importance of each cell and tissue through to the whole organism is explored alongside the methodologies used to understand these vital structures and functions.